A weighted fuzzy approach for green marketing risk assessment: Empirical evidence from dairy industry. (10th December 2021) - Azadnia, Amir Hossein; Geransayeh, Mohsen; Onofrei, George; Ghadimi, Pezhman
Abstract: The green marketing concept encompasses the consumers' perception and response to the green initiatives and activities that companies implement such as design for environment, green production systems and processes development, and green improvements in packaging. Despite the growing interest in the green marketing domain, few studies have been carried out on the risk assessment of green marketing implementation, especially in the dairy industry. In this study, using a developed integrated fuzzy decision-making methodology, the green marketing risk factors in the dairy industry are assessed. Firstly, the fuzzy analytic hierarchy process is used for weighting the identified risk assessment criteria. Then, a weighted fuzzy inference system is proposed for green marketing risk assessment. Finally, risk mitigation strategies are proposed to deal with the highly ranked risk factors. This research study fills the gaps in the literature by (1) proposing a comprehensive list of green marketing risk factors in the dairy industry, (2) developing a novel weighted fuzzy inference system approach for assessing those risk factors, and (3) providing a final ranking of the dairy industry risk factors together with risk mitigation strategies for the highly ranked risk factors. The level of environmental awareness in society was found as the most important risk factor followed by governmental policies, rules, and regulations for supporting green products risk factors. Finally, some remarks are concluded together with presenting the future works. Highlights: A comprehensive list of green marketing risks in the dairy industry is developed. A novel weighted FIS risk assessment approach is developed and utilised. The developed approach is validated using a case study in the dairy industry. A final ranking of the assessed risk factors & mitigation strategies are discussed.